2016
DOI: 10.1002/pds.4092
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of anti-diabetic medication use in patients with type 2 diabetes mellitus in England and Wales

Abstract: Purpose The purpose of this study is to characterise how Type 2 Diabetes Mellitus (T2DM) is treated in England and Wales and whether this adheres to 2009 National Institute for Health and Care Excellence (NICE) guidance on management of T2DM. Methods Data for T2DM patients aged 18+ years prescribed at least one anti-diabetic drug between 01/01/2000-30/06/2012 were extracted from the Clinical Practice Research Datalink.We examined the sequences in which anti-diabetic drugs were prescribed and, for patients on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
3
18
0
1
Order By: Relevance
“…This difference may be explained, at least in part, by lower metformin monotherapy usage in South-East Asia, the Eastern Mediterranean and the Western Pacific, where less than 50% of patients were prescribed metformin monotherapy at first line. The proportions of patients receiving metformin monotherapy as first-line treatment in Africa, the Americas and Europe were 83.6%, 77.1% and 67.1%, respectively; similar to the previous reports [22][23][24][25].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This difference may be explained, at least in part, by lower metformin monotherapy usage in South-East Asia, the Eastern Mediterranean and the Western Pacific, where less than 50% of patients were prescribed metformin monotherapy at first line. The proportions of patients receiving metformin monotherapy as first-line treatment in Africa, the Americas and Europe were 83.6%, 77.1% and 67.1%, respectively; similar to the previous reports [22][23][24][25].…”
Section: Discussionsupporting
confidence: 89%
“…The most common first-line therapy was metformin monotherapy in all regions. However, overall only 55.6% of all patients received metformin monotherapy at first-line, a lower proportion than has been reported in some recent retrospective observational studies conducted in Western countries [22][23][24][25]. In these studies, 65-91% of patients newly diagnosed with type 2 diabetes mellitus received metformin monotherapy as first-line treatment.…”
Section: Discussionmentioning
confidence: 83%
“…With the intention-to-treat analytic approach, patients in the basal insulin, TZD, and DPP-4i groups were followed for 4. 16,4.52, and 4.09 years, respectively, and similar results were found for most of the outcomes, including MACEs and all-cause mortality. However, the risk of ischemic stroke was significantly higher in the TZD group (HR 1.25, 95% CI 1.03-1.50) than the basal insulin group.…”
supporting
confidence: 78%
“…However, the initiation of insulin therapy is often delayed in clinical practice because most patients are reluctant to or inconvenienced by using injectable medications 10 .The role of basal insulin as an add-on antidiabetic agent remains unclear [11][12][13] . Previous studies have shown that the combination of metformin and sulfonylureas dominated in dual therapy in the early phase of disease management [14][15][16][17] , and other OHAs, such as thiazolidinediones (TZDs) and dipeptidyl peptidase-4 inhibitors (DPP-4is), are common treatment options after the failure of dual therapy 11,13,16 . Several observational studies compared insulin to OHAs and noted a significantly increased risk of CVDs or all-cause mortality associated with insulin 18-23 .…”
mentioning
confidence: 99%
“…Ninety percent of diabetes is type 2 diabetes, generally with obesity, deficiency in insulin secretion, and insulin resistance [ 4 ]. The treatment of diabetes mainly depends on hypoglycemic drugs such as insulin, sulfonylurea, metformin, α-glucosidase inhibitor, and thiazolidinediones, by increasing the insulin level, enhancing the insulin sensitivity, or decreasing the glucose absorption [ 5 , 6 ]. These drugs frequently present side effects such as weight gain, hypoglycemia, heart failure, and gastrointestinal problems [ 6 , 7 ], which drives us to develop novel agents.…”
Section: Introductionmentioning
confidence: 99%